NON-STATE PENSION SYSTEM IN UKRAINE: TRENDS AND PROBLEMS OF DEVELOPMENT - Smyrnova, Iryna; Khachikian, Sofiia (Economic scope, 2021)
The article considers the pension system of Ukraine in modern realities. The analysis of the state of pension provision of the population is carried out. It has been established, thanks to foreign experience, that such a pension system is able to provide the population with a much better standard of living after retirement than it is today. The necessity of improving the current pension system on the basis of the development of private pension provision in Ukraine is substantiated. It is established that the main benefits of this system are the provision of investment resources for the economy of Ukraine by attracting additional funds and the fact that it does not depend on the demographic situation. The main trends and features of the development of private pension funds based on the analysis of their activities over the past three years have been identified. It is determined that the influence of private pension funds is inherent both at the time of accumulation of contributions and at the time of investment, as well as at the stage of pension payment. It was found out that it is the accumulative pension system in Ukraine that will make it possible to establish a direct dependence of the amount of future pension benefits on the wishes of the working citizen, and not only on the state. It is noted that today the population does not show much interest in private pension provision due to low level of financial awareness of the population and high distrust of private pension funds due to fear of non-return of citizens’ own funds. It is established that despite these factors that hinder the development of private pension funds in Ukraine, their functioning is one of the ways to improve the quality of life of people of retirement age. It is determined that only under the conditions of effective organization, profitable investment, ensuring reliability and proper regulation; private pension provision will develop and increase the level of income of pensioners. It is investigated that the development of non-state pension structures is impossible without increasing the income of the population and further improving the state of the financial market.